Drive Circuit of Three-level IGBT Module Based on 2SC0108T Chip - ZHANG Honghao; ZHU Shiwu; TANG Zhou; WU Hengliang; LIU Zhaoyi; ZHAO Xianggui (Kongzhi Yu Xinxi Jishu)
A novel three-level IGBT driver board was presented based on 2SC0108T driver chip. It possesses the functions of undervoltage protection, short-circuit protection, etc. The theories were validated by the precise PSpice model on the terms of PWM signal conditioning circuit and fault feedback circuit. The hardware of this driver board was applied in the F3L400R12PT4 IGBT module’s chopping test and shortcircuit test, and the results show that this driver board is valid and reliable in engineering application.